Sensitivity of a 3D Shelf Sea Ecosystem Model to Parameterizations of the Underwater Light Field - Thewes, Daniel; Stanev, Emil V.; Zielinski, Oliver (Frontiers in Marine Science, 2020)
The inherent optical properties of water over the North Sea vary widely in space and time. Their impact on the performance of 3D-ecosystem-model of the North Sea needs to be critically evaluated, which is the major research issue in the present paper. We have performed a sensitivity analysis to a modification of a common approach of light treatment that is both valid for the North Sea, as well as computationally efficient to implement and run within a 3D-ecosystem-model. Using a coupled hydrodynamical model (Regional Ocean Modelling System, ROMS) and biological model (Carbon Silicate and Nitrogen Ecosystem model, CoSiNE), we found that simple changes to the original parameterization can yield significant improvements. ROMS is shown to be suitable for application in the North Sea. The model accurately reproduces the seasonal cycle of primary production in terms of timing and magnitude, while still being more affordable in comparison to full hyperspectral treatment or solving the radiative transfer equation. The modification introduces vertically increasing attenuation that is stronger in shallow domains, in a way that is similar to attenuation due to sediment. The resulting reduction of light availability leads to strongly reduced phytoplankton growth in shallow areas with high turbidity. Areas of depths between $50m$ and $100m$ show greatest relative change with respect to their total ranges, while the deepest areas remain largely unchanged. We found that the consideration of spacial varibility of light attenuation is necessary when modelling a heterogeneous domain, such as the North Sea.